Hubungan antara Karakteristik Individu dengan Iklim Keselamatan Kerja Pekerja Unit Produksi PT Y Gresik - Tahyudin Uzi Safaat (Pusat Riset dan Inovasi Nasional, 2026)
Safety climate is a workers' perception of the values, policies, and safety procedures that companies implement in prioritizing safety in the workplace. This study aims to analyze the relationship between individual characteristics and safety climate in PT Y Gresik production unit workers. The type of research used is observational quantitative design with a cross-sectional approach. The research population is all production unit workers as many as 40 people with a total sampling technique. The independent variables in this study are individual characteristics (age, working period, and education level) and dependent variables, namely safety climate. The source of research data was obtained through the distribution of questionnaire sheets. The data analysis used was the Spearman correlation test. The results showed that safety climate and individual characteristics did not show a significant relationship with age (p=0.396, r=0.138), working period (p=0.915, r=-0.017), and education level (p=0.095, r=0.268) withl safety climate. It is suggested that companies can strengthen their management commitment and work safety systems to increase workers' positive perception of safety in the work environment.